The problems of birds as pests : (proceedings of a symposium held at the Royal Geographical Society, London, on 28 and 29 September 1967) - Murton, R. K.; Wright, E. N. (Ernest Nuttall) (Academic Press, 1968)
The Problems of Birds as Pests covers the proceedings of the symposium held at the Royal Geographical Society in London on 28 and 29 September 1967. The text focuses on the problems posed by birds on agriculture and air transport, as well as control of population, scaring techniques, and warning systems. The selection first discusses prospective considerations concerning bio-acoustics in relation to bird-scaring techniques and recent developments in bird scaring on airfields. Topics include system of behavior and hierarchy of signals, informative content of acoustic signals, and signal-noise.